The importance of monitoring adverse drug reactions in pediatric patients: the results of a national surveillance program in Italy. (September 2014) - Carnovale, Carla; Brusadelli, Tatiana; Zuccotti, GianVincenzo; Beretta, Silvia; Sullo, Maria Giuseppa; Capuano, Annalisa; Rossi, Francesco; Moschini, Martina; Mugelli, Alessandro; Vannacci, Alfredo; Laterza, Marcella; Clementi, Emilio; et al.
<x xml:space="preserve">Abstract</x> Objective: To gain information on safety of drugs used in pediatrics through a 4-year post-marketing active pharmacovigilance program. The program sampled the Italian population and was termed 'Monitoring of the Adverse Effects in Pediatric population' (MEAP). Research design and methods: Adverse drug reactions (ADRs) were collected for individuals aged 0 – 17 years treated in hospitals and territorial health services in Lombardy, Tuscany, Apulia and Campania; located to gain an appropriate sampling of the population. ADRs were evaluated using the Adverse Drug Reaction Probability Scale (Naranjo) and analyzed with respect to time, age, sex, category of ADR, seriousness, suspected medicines, type of reporter and off-label use. Results: We collected and analyzed reports from 3539 ADRs. Vaccines, antineoplastic and psychotropic drugs were the most frequently pharmacotherapeutic subgroups involved. Seventeen percent of reported ADRs were serious; of them fever, vomiting and angioedema were the most frequently reported. Eight percent of ADRs were associated with off-label use, and 10% were unknown ADRs. Analysis of these revealed possible strategies of therapy optimization. Conclusions: The MEAP project demonstrated that active post-marketing pharmacovigilance programs are a valid strategy to increase awareness on pediatric pharmacology, reduce underreporting and provide information on drug actions in pediatrics. This information enhances drug therapy optimization in the pediatric patients.